Secret seven adventure - "Blyton, Enid" (Hooder Children's Book: London, 2002)
A priceless pearl necklace has been stolen, and the Secret Seven witnessed the thief making his escape. But where has he hidden the necklace?
Keywords: Detective and mystery fiction